Leadership Style Analysis of The Head of The Center for Statistics (BPS) of Tulang Bawang Barat District - Valentinus Giovani Febrian (Universitas Pamulang, 2023)
The purpose of this study was to determine the application of the leadership style of the Head of the Central Bureau of Statistics (BPS) of Tulang Bawang Barat Regency. BPS is a Non-Ministerial Government Institution directly responsible to the President, with the vision of